Perbedaan Efektivitas Pengukuran Suhu Tubuh Menggunakan Termometer Air Raksa Melalui Aksila dan Termometer Membran Timpani pada Klien Demam di RS PKU Muhammadiyah, Yogyakarta 2005 - Zulkhah Noor; Erna Rochmawati; Eni Eni Marlina (Universitas Muhammadiyah Yogyakarta, 2005)
Body temperature is one of the indications of health status and it may be above normal. The average number of clients suffering from fever increases 35% each month. Knowing the body temperature is one of an effective ways to understand the vital symptoms before giving treatment. Thermometers which usually used to measure the body temperature are mercury and timpani membrane thermometers which each of them has its own characteristics. The aim of the study was to find the effectiveness of the two thermometers in measuring body temperature of clients suffering from fever in PKU Muhammadiyah Yogyakarta hospital.This is an observational study with cross sectional design. There were 30 respondents who suffer staying in recovery room. Their body temperatures were checked twice using mercury and timpani membrane thermometers in order to determine the result of measurement, effective time of the measurement and response toward safety level and clients comfort. The subject analysis used t- test and Me Nemar.There were 27 respondents (90%) felt more secure when measured by using mercury thermometer. Me Nemar test shows that mercury thermometer measures the body temperature saver than timpani membrane thermometer. There were 21 respondents (70%) felt more comfortable when their body temperatures were measured by using timpani membrane thermometer. Me Nemar test shows that timpani membrane thermometer measures the body temperature more comfortably. The average difference of the body temperature measured by using mercury thermometer (38,1 ± 0,7) and the average difference of the body temperature measured by using timpani membrane thermometer (38,3 ± 0,7) was ± 0,2. The t-test result shows that measuring the body temperature using mercury thermometer and timpani membrane thermometer does no have any significant difference.The time needed to measure the body temperature using mercury thermometer is 5 minutes while timpani membrane thermometer needs 2 seconds to indicate the body temperature. The clients felt more secure when their body temperature are measured using mercury thermometer. On the other hand, the clients felt more comfortable when their body temperatures are measured using timpani membrane thermometer. The result of the body temperature measured using mercury thermometer and timpani membrane thermometer does not have any significant differences.Suhu tubuh adalah salah satu indikator status kesehatan, perubahannya dapat melebihi nilai normal (demam). Rata-rata tingkat jumlah yang klien dengan demam sekitar 35% setiap bulannya. Tindakan keperawatan yang dapat dilakukan untuk pengkajian tanda vital yang cepat dan tepat yaitu dengan pengukuran suhu tubuh. Termometer yang sering digunakan yaitu termometer air raksa dan termometer membran timpani yang keduanya memiliki karakteristik tersendiri. Tujuan penelitian ini untuk mengetahui perbedaan efektivitas pengukuran suhu tubuh menggunakan termometer air raksa dan termometer membran timpani pada klien demam di RS PKU Muhammadiyah Yogyakarta.Jenis penelitian observasional dengan rancangan belah lintang. Sampel adalah klien demam yang dirawat di instalansi rawat inap sebanyak 30 responden. Subyek mendapatkan dua kali pengukuran dengan termometer air raksa dan termometer membran timpani untuk menentukan hasil pengukuran, waktu efektif pengukuran, dan respon terhadap tingkat keamanan dan kenyamanan. Analisa subyek menggunakan uji t-test dan McNemar.Sebanyak 27 orang klien demam (90%) merasa aman bila diukur dengan termometer air raksa. Uji McNemar, termometer air raksa mengukur suhu tubuh lebih aman. Sebanyak 21 orang klien demam (70%) merasa nyaman bila diukur dengan termometer membran timpani. Uji McNemar, termometer membran timpani mengukur suhu tubuh lebih nyaman. Perbedaan rata-rata pengukuran suhu dengan termometer air raksa (38,1±0,7) dan termometer membran timpani (38,3±0,7) ± 0,2. Uji t-test, hasil pengukuran suhu tubuh dengan termometer air raksa berbeda tidak bermakna dengan termometer membran timpani.Waktu efektif pengukuran suhu tubuh dengan termometer air raksa adalah 5 menit, sedangkan termometer membran timpani adalah 2 detik. Klien demam merasa lebih aman diukur dengan termometer air raksa. Klien demam merasa lebih nyaman diukur dengan termometer membran timpani. Hasil pengukuran suhu tubuh termometer air raksa berbeda tidak bermakna dengan termometer membran timpani.